The Case of Interactive Metaphor - Kiklewicz, Aleksander (Lingua Posnaniensis, 2012)
The author analyses the limits of metamorphosis, i.e. possibility of an utterance with idiomatic or non-conventional, disturbing selection requirements of syntagmatic components being considered as metaphorical. The phenomena of metaphor and metonymy are interpreted from the point of view of condensation of surface structure of a sentence, as well as from the point of view of intentional semantics. The author presents elements of metaphor theory as a pragmatic re-codification, treating metaphor as a kind of "multi-vocality" or an intertext.